Anxiety and depression among women living with HIV: prevalence and correlations - Yousuf, Abdilahi; Musa, Ramli; Md Isa, Muhammad Lokman; Mohd Arifin, Siti Roshaidai (Bentham, 2020)
Introduction: It has been found that HIV positive women are becoming increasingly affected by various illnesses, including Common Mental Disorders (CMDs) such as depression. Such comorbidity escalates the disease progression to the severe stage and commonly hinders treatment adherence. This study determined the prevalence of anxiety and depression amidst women living with HIV. Methods: Based on a cross-sectional and facility-based study, 357 HIV positive women were recruited using the systematic sampling technique from two public hospitals in Jijiga town, Ethiopia. The Hospital Anxiety and Depression Scale (HADS) was administered for screening, and followed by a pre-tested questionnaire that comprised of Perceived Social Support and HIV stigma. Results: The results revealed that the prevalence of both anxiety and depression amidst HIV positive women was 28.9% and 32.5%, respectively. In the multivariate analysis, it was discovered that lack of formal education, being divorced, unemployed, and earning a monthly income less than 1400 ETB (37.5 USD) were significantly associated with depression. Women with symptomatic HIV clinical stage III (AOR =2.06, 95% C.I (0.75-5.61), with CD4 cell count below 250 (AOR = 1.14, 95% C.I (0.57-2.28), and with co-infections (AOR= 1.04, 95% C.I (0.40-2.71) also suffered from depression. Conclusion: The study outcomes show that the prevalence of depression in women with HIV was 32.5%, but they were more likely to be depressed if they were illiterate, divorced, unemployed or had a financial burden. In addition, HIV positive women with less CD4 cell count and in the final clinical stage or suffered from a co-infection were also associated with depressive symptoms. This signifies the public health implications of psychological and cognitive morbidities of the illness among these women with chronic illnesses. Hence, future mental health interventions and HIV care should be integrated with substantial emphasis given to vulnerable groups, including HIV positive women.